How digital marketing can use a smart phone app to improve any business's bottom line - Manko, Barbara (SAGE Business Cases., 2022)
The marketing strategy of offering customer loyalty rewards has evolved with the use of technology. Instead of printing old-fashioned paper coupons, punch cards, and flyers to advertise special offers, customers can access their rewards through a customized app. The app functions as an all-in-one tool to attract customers, send offers, communicate specials, take orders, offer new products and services to existing customers, and so much more. During the restrictions of the COVID-19 lockdown, businesses found online communication soaring, with the ability to offer no-contact delivery of goods and services, and many businesses are keeping the technology they implemented during lock down because it is just good business. The use of application creation for digital marketing has the ability to supercharge sales by more effectively reaching the target audience and providing business analytics on users.